Biological characteristics of the japanese scad Decapterus maruadsi in Thuan An estuary, Thua Thien Hue Province - Anh, Tran Thi Ngoc; Huan, Nguyen Xuan; Thanh, Tran Trung; Nam, Nguyen Thanh (Academia Journal of Biology, 2019)
A total of 257 Decapterus maruadsi individuals of collected from Thuan An estuary in Phu Vang District, Thua Thien Hue Province were analyzed. Results showed that the fork length ranged from 90 mm to 215 mm (160.2 mm on average) and mainly in the 140–180 mm range (86.8 %). Of three age groups (0+ to 2+), the fished stock belongfrom is primarily to the 1+ age group (63.8%) and 0+ age group (28.8%). Of five stomach fullness levels (0 to 4), the second and fourth degree made up significantly proportions, being 29.6% and 31.5%, respectively. For the five fat levels (0 to 4), the fourth degree made up 86.0%.  The females to males ratio was 1.00 : 1.42.  von Bertalanffy’s growth model followed the equation: Lt = 203.77 × (1–e-0.3747(t+3.0272)).